Antioxidant properties of liquid smoke in precooked beef patties - R. Estrada-Munoz; Elizabeth A.E. Boyle; James L. Marsden (Kansas Agricultural Experiment Station Research Reports, 1997)
Liquid smoke (LS) effectiveness in controlling lipid oxidation and warmed-over flavor (WOF) in beef was investigated. Aroma scores, "Î±-thiobarbituri c acid (TBA) numbers, and pH values were lower (P<.05) in LS-treated beef patties than in patties without LS. LS has useful antioxidative properties in precooked ground beef patties at the normally recommended percentage of 1.5%. That should reduce undesirable flavor development and product loss.
Keywords: Cattlemen& #x27; s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Liquid smoke; Warmed-over flavor; Precooked beef patties